2000
DOI: 10.1097/00000374-200011000-00004
|View full text |Cite
|
Sign up to set email alerts
|

No Sex and Age Influence on the Expression Pattern and Activities of Human Gastric Alcohol and Aldehyde Dehydrogenases

Abstract: The results indicate that there is no significant effect of either sex or age on the expression pattern and activity of ADH and ALDH in the human gastric mucosa. The stomach ADH seems unlikely to account for possible variations in the first-pass metabolism of alcohol with regard to sex and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…The latter finding is consistent with the report of Vidal et al (1998). Furthermore, the activity in human stomach and colon was not influenced by sex and age (Yin et al, 1994;Lai et al, 2000). Our analysis found that the activity in human liver was similar in both sexes but slightly, although not significantly, decreased in older subjects.…”
Section: Aldh2 Gene Snps and The Metabolism Of Aldehydessupporting
confidence: 93%
“…The latter finding is consistent with the report of Vidal et al (1998). Furthermore, the activity in human stomach and colon was not influenced by sex and age (Yin et al, 1994;Lai et al, 2000). Our analysis found that the activity in human liver was similar in both sexes but slightly, although not significantly, decreased in older subjects.…”
Section: Aldh2 Gene Snps and The Metabolism Of Aldehydessupporting
confidence: 93%
“…Thus, the decreased activity of gastric Class III (-) ADH in women is consistent with the concentration effect of imbibed alcohol and can explain the lack of gender effects on alcohol bioavailability in studies performed with low concentrations of imbibed alcohol (Ammon et al, 1996;Oneta et al, 1998). In Chinese subjects, a lack of gender effects on ADH activity was reported by Yin et al (1997) and Lai et al (2000) with 500 mM ethanol. This could be due to the less than 25% prevalence of -ADH expression, because the activity of this isozyme (called -ADH by this group) is a major contributor to ethanol oxidation at 500 mM.…”
Section: Discussionsupporting
confidence: 62%
“…Although ADH activity measured at 16 mM ethanol was not significantly affected by age and sex, both factors affected ADH activity measured at 580 mM (Seitz et al, 1993), a concentration like that occurring in the stomach after drinking alcohol (Halsted et al, 1973). In Asian subjects who frequently have a low activity of gastric -ADH isozyme Dohmen et al, 1996;Yin et al, 1993), Harada and Okubo (1993) found less -ADH in Japanese women than in men, whereas no gender differences were detected in Chinese (Lai et al 2000;Yin et al, 1997).…”
mentioning
confidence: 79%
“…Some authors negate these differences [11,13,[24][25][26][27][28][29]; however, the majority of the studies report a significantly higher elimination rate in women [4][5][6][7][8][9][10][11][12][13][14][15][16][17]23,30]. Admittedly, the possible causes discussed in the respective gender-related differences are quite varied.…”
Section: Discussionmentioning
confidence: 99%